Robust catalysis of hierarchically nanoporous gold for CO2 electrochemical reduction. (1st January 2023) - Yu, Tianshui; Zhou, Xiangji; Chen, Yu; Chen, Jin; Yuan, Songliu; Zhang, Zhen; Qian, Lihua; Li, Song
Highlights: The layer of nanoporous structure created by pulse potential can obtain a high selectivity of CO. Hierarchically porous structure is an effective structure to improve mass transport. Hierarchically porous gold exhibits robust durability of specific current density in 22 h CO2 ER. Outstanding durability is well related to the conversion of some crystal facets during CO2 ER. Abstract: Catalytic activity and durability are crucial parameters of nanoporous gold for CO2 electrochemical reduction, where multiple protons and electrons are involved. Mass transport within porous channels and active sites onto skeletons surface of nanoporous gold are considered as basic requirements to enhance these comprehensive performances. While the evolution of active site at atomic scale is a remaining issue to understand intrinsic mechanism of the decaying catalysis. In this work, we configure hierarchically nanoporous gold (HNPG) with high Faradaic efficiency for CO conversion of 96%, which results from abundant of step sites and (110) facets. High current density of 0.2 mA/cm 2 mainly results from high fraction of active sites onto nanoscale skeletons and high volume of hierarchically nanoporous channels. Besides high activity, the HNPG also exhibits robust durability, which is evidenced by its 22% reduction of specific current density for CO after 22 h CO2 ER in comparison with 55% reduction of nanoporous gold (NPG) with nanoporous channel. By investigating the detailed feature of surface contour, outstanding durability in the HNPG is well related to the conversion of some crystalline facets with low activity toward (110) facets with high activity during CO2 ER. This behavior is completely different from the evolution of surface contours in NPG, where step sites and (110) facets partially converse into the other facets with inferior catalysis. Graphical abstract: Outstanding durability in the HNPG is well related to the conversion of some crystal facets with low activity toward (110) facets with high activity during 22 CO2 ER as high as 90%. Image, graphical abstract